Cities' economic development efforts in a changing global economy: content analysis of economic development plans in Ontario, Canada. Issue 3 (6th April 2017) - Cleave, Evan; Arku, Godwin; Chatwin, Merlin
Abstract : Over the past few years, cities have been increasingly adopting a written plan to guide economic development processes. This is in sharp contrast to past practices which were haphazard and unsystematic. So far, there has been no comprehensive overview of the policies, strategies and focus of these written documents. Focusing on the Province of Ontario, Canada, we undertook a systematic content analysis of the most recent documents for each city. Specific codes were developed for the analysis of the documents. While the majority of cities in Ontario were identified as having codified a formal economic development plan (a plan was identified in 41 of 51 cities), there was considerable variability in how the plans were developed (such as through the use of private consultants) and presented, with noticeable differences in the information given about the community, complexity of analysis conducted and the details on the economic development policies that are being pursued. Despite the range of document formats, there was notable uniformity in the content of the policy directives that were presented. In terms of economic development focus, traditional manufacturing is essentially ignored in favour of attracting advanced manufacturing and knowledge‐based industries. Additionally, due to the extensive reliance on private external consultants, the plans have a homogenous nature, where contemporary ideas such as diversification, place branding and marketing, downtown redevelopment, focus on creative and knowledge industries, and tourism are constantly regurgitated. Conspicuously missing among the strategies were regional collaborations and cluster development. Although the adoption of a written plan represents an important milestone in local economic development policymaking, a number of key limitations were identified within the current documents, and the paper offers direction for a more effective future policy development.